Criminological Review of Children as Perpetrators of Violent Theft - Mayusla, Nisha; Simatupang, Nursariani (Indonesian Journal of Law, 2026)
Crime today knows no age, and one of the most alarming forms for society is theft accompanied by violence, which is committed not only by adults but also by children. In such cases, children may be subject to sanctions under the applicable criminal laws in Indonesia. These acts can result in injuries ranging from minor to severe and may even lead to the death of victims or members of the public. This study employs an empirical juridical research method, using primary data, secondary data, and Islamic legal sources. Data collection techniques include interviews conducted at the Binjai Police Resort (Polres Binjai) and documentation studies. Based on the findings, the perpetrators’ modus operandi involves approaching the victim closely, kicking the victim until they fall, and then using a machete to slash or injure parts of the victim’s body. The factors contributing to violent theft committed by children include religious factors, economic conditions, family environment, education, peer influence, drug abuse, and curiosity or experimentation. Efforts to address this issue in Binjai City include pre-emptive measures, such as police outreach programs in schools to educate students not to engage in harmful behaviors like joining motorcycle gangs; preventive measures, including traffic regulation and routine patrols; and repressive measures, such as the arrest of offenders.